2009
DOI: 10.1097/pts.0b013e31819d65c2
|View full text |Cite
|
Sign up to set email alerts
|

A Patient Safety Objective Structured Clinical Examination

Abstract: Results suggest increased systems thinking and inculcation of a culture of safety among residents exposed to a patient safety curriculum. The main weaknesses of the study are its small size and suboptimal design. Much further investigation is needed into the effectiveness of patient safety curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…The most frequently used instructional approaches in the studies were lectures, [14][15][16][17][18][19][20][21][22][23][24] case-based exercises, 16,20,[22][23][24][25][26][27][28][29] active-learning exercises, 14,[16][17][18][19][24][25]28,[30][31] and discussion. [14][15]17,21,[26][27]31,32 Simulation exercises were common, including the use of standardized patients 29,[31][32][33] and role-plays. 17,18,21 Projects and presentations also were used as a way to engage participants with patient safety topics.…”
Section: Instructional Pedagogymentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used instructional approaches in the studies were lectures, [14][15][16][17][18][19][20][21][22][23][24] case-based exercises, 16,20,[22][23][24][25][26][27][28][29] active-learning exercises, 14,[16][17][18][19][24][25]28,[30][31] and discussion. [14][15]17,21,[26][27]31,32 Simulation exercises were common, including the use of standardized patients 29,[31][32][33] and role-plays. 17,18,21 Projects and presentations also were used as a way to engage participants with patient safety topics.…”
Section: Instructional Pedagogymentioning
confidence: 99%
“…15,22,[28][29]32,33,36 In 2 of the studies, a multiple station objective structured clinical examination (OSCE) was used to assess students' performance on a variety of patient safety issues including detecting a medication error, addressing an adverse event or deficient care, and conducting a root cause analysis. 28,33 Participants performed well in both studies (100% pass rate) in areas including: root cause analysis, prescription error, negotiation, and evidencebased medicine stations 33 or improved error detection and disclosure skills and identification of deficiencies of care.…”
Section: Assessmentmentioning
confidence: 99%
“…The duration of such courses was 1–2 full work days for each cohort. Half of the papers reported pilot one-off courses and presented the findings (4) 40 41 45 46. Patient safety modules that made up part of a regular training programme (5) and naturally occurring learning moments (1) were also reported in the literature 48–53.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the proportion of participants who considered the incident in the vignette worth reporting went from 15% prior to the course to 43% post course. Singh et al 46 reported that an Objective Structured Clinical Examination developed to assess error detection and disclosure skills was a feasible strategy, but that additional work to ensure the reliability and validity of each component is needed. None of the measures employed in relation to any of the training strategies demonstrated evidence of a causal relationship between participation and the outcome assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Our very positive experience with the proposed approach in the domains of medication safety, falls safety, postoperative pain, and assessment of EMR introduction has demonstrated that it also promotes ACGME's core competencies [3] [57] [58] of "system-based practice and practice-based learning and improvement". Our objective is to prepare the minds [56] of teams and the individuals forming them, through our prospective methodology that invokes "Improvement Science" and refrains from reductionism.…”
Section: Discussionmentioning
confidence: 99%